2000
DOI: 10.1021/ic000159c
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Assignment of the g Tensor of [Fe(OEP)(NO)] by Single-Crystal EPR

Abstract: Single-crystal EPR measurements have been performed on the triclinic form of [Fe(OEP)(NO)] (Ellison, M. K.; Scheidt, W. R. J. Am. Chem. Soc. 1997, 119, 7404) and on the isomorphous cobalt derivative [Co(OEP)(NO)] (Ellison, M. K.; Scheidt, W. R. Inorg. Chem. 1998, 37, 382) which has been doped with [Fe(OEP)(NO)]. Principal values of the g tensor determined at room temperature are gmax = 2.106, gmid = 2.057, and gmin = 2.015. The principal direction associated with the minimum g value lies 8 degrees from the Fe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 26 publications
9
49
0
Order By: Relevance
“…The EPR parameters of 1 NO -LS and 2 NO -LS closely align with those computed for S =1/2 [ 2-NO ] 5C , as well as those observed for 5C NO adducts of ferrous-porphyrin complexes. 97100 Thus, we conclude that the observed low-spin signal is due to dissociation of the trans imidazole donor in a fraction of the {FeNO} 7 adducts prepared at low temperature.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The EPR parameters of 1 NO -LS and 2 NO -LS closely align with those computed for S =1/2 [ 2-NO ] 5C , as well as those observed for 5C NO adducts of ferrous-porphyrin complexes. 97100 Thus, we conclude that the observed low-spin signal is due to dissociation of the trans imidazole donor in a fraction of the {FeNO} 7 adducts prepared at low temperature.…”
Section: Resultsmentioning
confidence: 71%
“…Importantly, the calculations are consistent with prior studies of low-spin {FeNO} 7 complexes, both heme and nonheme, which have revealed that certain spin-Hamiltonian parameters are diagnostic of coordination number. 97100 Specifically, the g x -values of 6C species are always less than the free-electron value ( g e = 2.002), whereas g x > g e for 5C {FeNO} 7 species. Additionally, the A -tensors of 6C complexes exhibit relatively large anisotropy and a dominant A y -value, whereas 5C complexes possess relatively isotropic 14 N A -tensors in which the A x -value is the largest component (Table 3).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For 5C complexes, the N–O stretch typically lies between 1675 and 1700 cm −1 , whereas for 6C complexes, the N–O stretch occurs at ~1630 cm −1 . Low-temperature EPR spectroscopy studies conducted by several authors reveal interesting differences between the 5C and 6C iron(II) porphyrin NO adducts [60, 61]. Hyperfine lines resulting from the bound nitrogen of NO are observed at the lowest g value (g min) in 5C ferrous-heme nitrosyls.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1) and tetrahydrothiophene (a thioether) are presented in this study. The obtained data are correlated to the EPR spectra of 1 itself and of the corresponding adduct with 1-methylimidazole (1-MI) [21][22][23][24][25][26] as well as EPR data of NO adducts of ferrous P450 and P450nor [15,16]. Density functional (DFT) calculations on the simplified model [Fe(P)(SMe)(NO)] À (P = simplified Porphyrin ligand) are then used to explore the general properties of Fe(II)-NO complexes with trans S-donor ligands as they occur in the P450 enzymes (bacterial P450cam, liver microsomal P450 LM and P450nor) in detail.…”
Section: Introductionmentioning
confidence: 99%